Sexually transmitted infections on the border between Brazil and French Guiana - Nacher, Mathieu; Divino, Flavia; Leborgne, Cyril; Correa, Valmir; Rabier, Sébastien; Lucarelli, Aude; Rhodes, Sophie; Gaillet, Mélanie; Malafaia, Dorinaldo; Rousseau, Cyril; Sanna, Alice; Gomes, Margarete; et al. (Frontiers in Public Health, 2023)
Purpose The border between the State of Amapa, Brazil, and French Guiana is mostly primary forest. In the Oyapock basin, socioeconomic circumstances have fueled sex work, gold mining and the circulation of sexually transmitted infections. Given the lack of comprehensive data on this border area, we describe the different sexually transmitted infections along the Brazil/French Guiana border and the testing and care activity. Methods We conducted a review of the available scientific and technical literature on sexually transmitted infections in this complex border area. Temporal trends were graphed and for Human Immunodeficiency Virus (HIV) we estimated incidence using the European Center for prevention and Disease Control modeling tool. Results Until 2019, 26 of the 46 HIV-infected patients followed and treated in Saint Georges de l'Oyapock were residing on the Brazilian side in Oiapoque. Virological suppression was only achieved for 75% of treated patients; but dropped to 62% during the COVID-19 epidemic. In 2019, cooperation efforts allowed HIV care in Oiapoque, resulting in the transfer of Brazilian patients previously followed on the French side and a substantial increase in the number of patients followed in Oiapoque. The average yearly HIV serological testing activity at the health center in Saint Georges was 16 tests per 100 inhabitants per year; in Camopi it was 12.2 per 100 inhabitants. Modeling estimated the number of persons living with HIV around 170 persons, corresponding to a prevalence of 0.54% and about 40 undiagnosed infections. The model also suggested that there were about 12 new infections per year in Saint Georges and Oiapoque, representing an HIV incidence rate of 3.8 cases per 10,000 per year. HPV prevalence in Saint Georges ranges between 25 and 30% and between 35 and 40% in Camopi. Testing activity for other sexually transmitted infections markedly increased in the past 5 years; the introduction of PCR for chlamydiasis and gonorrhea also had a substantial impact on the number of diagnoses. Conclusions The ongoing cooperation between multiple partners on both sides of the border has led to remarkable progress in primary prevention, in testing efforts, in treatment and retention on both sides of the border. In a region with intense health professional turnover, nurturing cooperation and providing accurate assessments of the burden of sexually transmitted infections is essential to tackle a problem that is shared on both sides of the border.